Adverse childhood experiences and deviant peer affiliation among Chinese delinquent adolescents: the role of relative deprivation and age - Wang, Yuepeng; Meng, Weijie (Frontiers in Psychology, 2024)
Background: Deviant peer affiliation is considered a potential risk factor for adolescent delinquency. Due to the serious situation of adolescent delinquency in China, it is necessary to investigate the mechanisms by which adolescents associate with deviant peers. Objectives: The purpose of this study was to examine the association between adverse childhood experiences (ACEs) and deviant peer affiliation, the mediating effect of relative deprivation, and the moderating effect of age in a sample of Chinese delinquent adolescents. Methods: 542 Special School students aged 11-18 years were interviewed and completed questionnaires, including demographics, adverse childhood experiences, deviant peer affiliation, and relative deprivation. Results: (1) After controlling for gender, adverse childhood experiences and deviant peer affiliation were significantly and positively associated among delinquent adolescents.(2) The effect of ACEs on deviant peer affiliation was mediated by relative deprivation. (3) Age played a moderating role not only in the relationship between ACEs and relative deprivation, but also in the indirect relationship in which ACEs influence deviant peer affiliation through relative deprivation; specifically, the indirect effect of ACEs influencing deviant peer affiliation through relative deprivation was stronger in early adolescence compared with late adolescence. Conclusions: Overall, early ACEs play an important role in deviant peer affiliation among delinquent adolescents and relative deprivation is an important mediating variable. The results of the present study emphasize the importance of cognitive interventions for delinquent adolescents who experience ACEs in early adolescence,